NÜZHUBO AND HER “BROTHERS”: STREAMING LIFE AND MEDIATING INTIMACY AT SCALE - Gu, Jingyi (AoIR Selected Papers of Internet Research, 2021)
In this paper, I consider live/life streaming as a mediated venue for making social relationships and a mediatized world constituted of diverse livelihoods. Drawing from my digital ethnography on two Chinese live streaming platforms Inke and Huajiao, I document the emergence of narratives, performances, and interactions that are either sexually suggestive or have gendered implications. I identify patterns of emotional expression and self-disclosure that lie within these interactions and analyze their alignment with and distinction from those that have been considered within the existing theorization of intimacy. In doing so, I examine how live/life streaming constructs scalable “mediated intimacy,” in the one-versus-many semi-public setting, through nurturing gendered performances and building subtle sexual tension between its participants.